The Influence Of Providing Kb Counseling On Knowledge Of Women Of Reproductive Age About 2-Month Kb Injection At PMB Nining Setiawan Indragiri Hulu District Year 2023 - Meria Turnip; Nining Setiawati; Reni Aprinawaty Sirait (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
The difficulty in determining the choice of contraceptive type is experienced by many prospective KB acceptors Caused by ignorance about the various advantages and disadvantages or side effects of each method of contraception. Efforts to overcome these problems require an effort to provide counseling or Information and Education (IEC) to each prospective family planning acceptor. This study aims to determine the effect of providing family planning counseling on the knowledge of women of reproductive age about 3-month family planning injections at PMB Nining Setiawan in 2023. This type of research uses a quasy experimental research design with a one group pretest posttest design. The population of this study were all women of childbearing age who used 3-month family planning injections at PMB Nining Setiawan. The sampling technique used purposive sampling based on the inclusion and exclusion criteria of 30 people. The research instrument used a questionnaire sheet which was analyzed using paired t-tests. The results showed that there was an effect of providing family planning counseling on the knowledge of women of childbearing age about 3-month family planning injections at PMB Nining Setiawan Indragiri Hulu District in 2023 with a p-value = 0.000 (p<0.005). It is hoped that midwives can improve counseling or communication, information, and education (IEC) about family planning injections so that women of childbearing age will increase their knowledge so that they can take appropriate action in family planning.